PEMBELAJARAN TARI KREASI PADA MATA PELAJARAN SENI BUDAYA MENGGUNAKAN MEDIA AUDIO VISUAL DI KELAS X MA BABUL FALAH KECAMATAN BELIDA DARAT - Aliza Lestari Widyanti; Treny Hera; Nofroza Yelli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem in this research is "How is the learning of creative dance in arts and culture subjects using audio-visual media in class X MA Babul Falah, Belida Darat District?". This study aims to identify and describe the Learning of Creative Dance in the Subject of Cultural Arts Using Audio Visual Media in Class X MA Babul Falah, Belida Darat District. The method used in this research is descriptive qualitative. The object of this study was the learning of Creative Dance in the subject of Cultural Arts which was carried out by the Class X Cultural Arts teacher using audio-visual media at MA Babul Falah. Data collection techniques used in this research are observation, interview and documentation techniques. Learning creative dance in arts and culture subjects using audio-visual media is known from the results of research data that has been carried out by researchers through observation of interview data and documentation data showing that the learning process of creative dance in arts and culture subjects uses audio-visual media in class X MA Babul Falah Belida Darat sub-district is running quite well, it can be seen in the assessment aspects, namely lesson planning, implementation and evaluation of learning. Teachers in creative dance learning activities always motivate students to get excited, and the conditions of the facilities and infrastructure are quite adequate and very supportive in the teaching and learning process.